Effects of combination therapy with mitiglinide and voglibose on postprandial plasma glucose in patients with type 2 diabetes mellitus - Konya H; Katsuno T; Tsunoda T; Yano Y; Kamitani M; Miuchi M; Hamaguchi T; Miyagawa JI; Namba M (Diabetes, Metabolic Syndrome and Obesity, 2013)
Hiroyuki Konya,1 Tomoyuki Katsuno,2 Taku Tsunoda,1 Yuzo Yano,1 Mai Kamitani,1 Masayuki Miuchi,2 Tomoya Hamaguchi,3 Jun-Ichiro Miyagawa,2 Mitsuyoshi Namba2 1Department of Internal Medicine, Ashiya Municipal Hospital, Ashiya, Hyogo, Japan; 2Division of Diabetes, Endocrinology and Metabolism, Department of Internal Medicine, Hyogo College of Medicine, Nishinomiya, Hyogo, Japan; 3Division of Innovative Diabetes Treatment, Hyogo College of Medicine, Nishinomiya, Hyogo, Japan Abstract: Patients with diabetes mellitus are at increased risk from cardiovascular-related morbidity and mortality as compared with healthy individuals. An association between the postprandial metabolic state and atherogenesis has been observed in patients with diabetes mellitus. In the Study to Prevent Non-Insulin-Dependent Diabetes Mellitus (STOP-NIDDM), treatment with an α-glucosidase inhibitor (α-GI) in patients with impaired glucose tolerance not only reduced the rate of conversion from impaired glucose tolerance to type 2 diabetes mellitus (T2DM), but was also associated with a reduction in the risk of cardiovascular events. These results suggested the importance of treating postprandial hyperglycemia in the early stages of T2DM. Glinides are rapid and short-acting insulin secretagogues that bind to the sulfonylurea receptors on pancreatic β-cells to facilitate rapid insulin secretion, restore postprandial early insulin secretion, and reduce the postprandial glucose spike. Moreover, α-GIs reduce postprandial hyperglycemia and insulin secretion by delaying the digestion of carbohydrates and polysaccharides in the small intestine. Then, both glinides and α-GI have beneficial effects for treating patients with T2DM and impaired glucose tolerance. Considering the ameliorating effects of these drugs on postprandial metabolic disorders, combinations of glinides and α-GI might constitute a promising therapeutic strategy for managing patients with T2DM, and also appear to be suitable for Japanese people, who consume more carbohydrates, such as polished rice, than Caucasians. It has recently been reported that combined use of mitiglinide and voglibose reduces postprandial insulin secretion and blunts diurnal glycemic changes in T2DM patients. This therapy can thus be regarded as being suitable for achieving strict postprandial glycemic control. In this report, we outline the effects of this combination therapy on postprandial plasma glucose and assess its safety. Keywords: mitiglinide, voglibose, combination therapy, type 2 diabetes mellitus, postprandial hyperglycemia